Peningkatan Availability Overall Equipment Effectiveness (OEE) Mesin Vertical Milling 3 Axis Melalui Integrasi Failure Mode and Effect Analysis (FMEA) dan Preventive Maintenance - Saptianhadi Saptianhadi; Tiaradia Ihsan (Universitas Batanghari Jambi, 2026)
This study aims to improve the Availability value in calculating the Overall Equipment Effectiveness (OEE) of a 3-Axis Vertical Milling machine at PT. XYZ. Low Availability value is an indicator of frequent unplanned downtime, which significantly hinders productivity. The proposed approach is the integration of the Failure Mode and Effect Analysis (FMEA) method with the implementation of a structured Preventive Maintenance (PM) program. FMEA is used to identify and prioritize potential failure modes in machine components based on the Risk Priority Number (RPN) value, which is obtained from the multiplication of Severity, Occurrence, and Detection. The FMEA results indicate that critical failure modes are dominated by problems in the spindle system, cooling system, and axis movement servo system, with the highest RPN values. Based on these critical findings, a customized PM program was developed, including scheduled inspections, relubrication, and component replacement before failure occurs. After the implementation of the PM program during the observation period, the average Availability value of the 3-Axis Vertical Milling machine increased from 63% to 74%. This increase in availability contributed to an increase in the total OEE value. This study demonstrated the effectiveness of combining FMEA and preventive maintenance as a robust strategy for minimizing unplanned machine downtime, thereby optimizing equipment performance and increasing operational competitiveness.